Transient relay function of midline thalamic nuclei during long-term memory consolidation in humans - Thielen, Jan-Willem (Learn Mem, 2015)
To test the hypothesis that thalamic midline nuclei play a transient role in memory consolidation, we reanalyzed a prospective functional MRI study, contrasting recent and progressively more remote memory retrieval. We revealed a transient thalamic connectivity increase with the hippocampus, the medial prefrontal cortex (mPFC), and a parahippocampal area, which decreased with time. In turn, mPFC-parahippocampal connectivity increased progressively. These findings support a model in which thalamic midline nuclei serve as a hub linking hippocampus, mPFC, and posterior representational areas during memory retrieval at an early (2 h) stage of consolidation, extending classical systems consolidation models by attributing a transient role to midline thalamic nuclei.